Beyond Intervention: Shaping Policy for Addressing Persistence and Relapse of Severe Problem Behavior. (March 2017) - Podlesnik, Christopher A.; Kelley, Michael E.
Individuals diagnosed with autism spectrum disorder (ASD) and other developmental disabilities are at risk of engaging in severe problem behavior, including aggression and self-injury. Severe problem behavior is an obstacle to proper education and integration into society. Therefore, eliminating severe problem behavior is key to long-term academic and social success. However, problem behavior can be persistent in the face of interventions and likely to relapse following successful intervention. This article describes basic and translational research relevant to understanding what influences the persistence and relapse of severe problem behavior in individuals diagnosed with ASD and other developmental disabilities. Investing in research to better understand persistence and relapse will pay dividends for clients, parents, clinicians, and society in general.